Healthy lifestyle behaviors and transitions in frailty status among independent community-dwelling older adults: The Yabu cohort study. (June 2020) - Abe, Takumi; Nofuji, Yu; Seino, Satoshi; Murayama, Hiroshi; Yoshida, Yuka; Tanigaki, Tomomi; Yokoyama, Yuri; Narita, Miki; Nishi, Mariko; Kitamura, Akihiko; Shinkai, Shoji
Highlights: 30.1% of the present community-dwelling adults were frail at baseline. 69.4% of older adults were non-frail at both baseline and the follow-up survey. 15.2% of frail older adults at baseline were non-frail at the follow-up survey. Healthy lifestyle behaviors helped prevent incident frailty and adverse events. Farming, intellectual activity, and social participation improved frailty status. Abstract: Frailty is a dynamic condition that can worsen or improve. Although previous studies have identified demographic and intrinsic factors associated with transitions in frailty status, less evidence is available regarding associations with daily activities. This longitudinal study examined associations of behavioral factors with incident frailty, adverse events (e.g. residence in a nursing home, hospitalization, and death), and frailty improvement among older adults. The analysis included data from 3, 769 independent older adults aged 65 years or more (mean age, 76.3 ± 7.2years; proportion of frail participants, 30.1%) from the Yabu cohort study (baseline, 2012; follow-up, 2017). The Kaigo-Yobo Checklist, a standardized questionnaire, was used to assess frailty status (non-frail or frail) and seven behavioral factors: farming, shopping, exercise, eating habit, intellectual activity, social participation, and smoking. At the 5-year follow-up survey, the proportions of participants transitioning from non-frail to frail, from non-frail to incident adverse events, from frail to non-frail, and from frail to incident adverse events were 16.8%, 13.9%, 15.2%, and 50.1%, respectively. In the analysis of non-frail participants, farming, exercise, intellectual activity, and social participation were associated with lower odds of becoming frail and experiencing adverse events. In the analysis for frail participants, farming, intellectual activity, and social participation were significantly associated with improvement in frailty status, and farming, shopping, and social participation were associated with lower odds of incident adverse events. These findings suggest that farming, healthy daily activities, and social participation help improve and prevent frailty/adverse events.